CHEMSEX: DIGITAL, CHEMICAL AND COMMUNAL INFRASTRUCTURE OF DISINHIBITION - Hakim , Jamie; Møller, Kristian; Florêncio, João; Murphy, Dean; Race, Kane; Pienaar, Kiran; Lea, Toby (AoIR Selected Papers of Internet Research, 2019)
Since the early days of digital media studies, it has been widely understood that trust in digital technologies has been indispensable for the operation of queer communities. Attaining access to _disinhibition_ is central to queer world-making: not only through coming “out”; and dancing at the gay club, but also by chemically altering your state of mind through alcohol and drug consumption. This panel explores queer ‘digital infrastructures of disinhibition’ through a digitally mediated sexual practice that has attracted significant attention over the last decade: ‘chemsex’, when gay and bisexual men use locative social media such as hook-up apps to organise group sex encounters where certain recreational drugs are consumed. Chemsex is a socio-sexual practice that to an overwhelming degree is _constructed_, _negotiated_, _enacted_, _maintained_ and _critiqued_ via digital platforms. Hook-up apps are key to facilitating chemsex encounters because they allow for instant access to nearby subjects who can join the chemsex event; porn platforms and video conferencing tools lend their affordances to the visual culture and consumption of chemsex. At the same time as digital media intervenes in chemsex subjectivity, so do the recreational drugs. Instead of treating the “effects” of media and drugs on the participating bodies as separated elements, this panel explores what can be achieved analytically if we think of them as co-constituting chemsex. To do so we conceptualize contemporary gay culture as an emerging assemblage depending on _digital_, _chemical_, and _communal_ infrastructures and the ways they are practiced, experienced, policed and transformed. The panel explores both the emergence and practice of chemsex, as well as what kinds of queer futurity chemsex events might offer, what “ways of feeling” emerge, and the subjectivities it produces, including the extent to which they might be considered to disturb, disrupt or, conversely, consolidate homonormative sociabilities and realities.